Church Construction as a Proxy for Economic Development: the Medieval Settlement Expansion Phase in the Peloponnese - Papadaki, Maria (Journal of Greek Archaeology, 2021)
The Peloponnese, with its diverse and varied landscapes, positioned at the crossroads of land and sea connections between West and East, and having a rich archaeological and historical heritage, is one of the most significant regions of the Mediterranean world. Yet, while the special qualities of the region’s landscape are well known to geologists and environmentalists, the evolution of its historical sites and landscapes is much less understood. There has been a prioritization of certain periods, sites, and types of data – with a tendency to focus on the Classical and earlier periods – which has resulted in a disparity in the evidence collected for the various periods of its past. The importance of the medieval landscape is fundamental, as during this period the structure of the modern natural and cultural landscape took shape, such as the patterns of agricultural exploitation and settlement distribution. The medieval landscape formed a dynamic backdrop to people’s daily lives, providing the basis for their sense of place and identity.